2016
DOI: 10.1016/j.neuron.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Reprogramming for CNS Repair: Regenerating Neurons from Endogenous Glial Cells

Abstract: Neuroregeneration in the central nervous system (CNS) has proven to be difficult despite decades of research. The old dogma that CNS neurons cannot be regenerated in the adult mammalian brain has been overturned; however, endogenous adult neurogenesis appears to be insufficient for brain repair. Stem cell therapy once held promise for generating large quantities of neurons in the CNS, but immunorejection and long-term functional integration remain major hurdles. In this perspective, we discuss the use of in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
114
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(114 citation statements)
references
References 127 publications
(176 reference statements)
0
114
0
Order By: Relevance
“…Neuronal conversion can be achieved by several neurogenic transcription factors (Li and Chen, 2016). Besides NeuroD1, Sox2, Ngn2, and Ascl1 have all been reported to convert glial cells into neurons (Gascon et al, 2016;Grande et al, 2013;Guo et al, 2014;Heinrich et al, 2014;Liu et al, 2015;Niu et al, 2013;Su et al, 2014).…”
Section: Distinct Functions Of Neurod1 During Neuronal Conversionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neuronal conversion can be achieved by several neurogenic transcription factors (Li and Chen, 2016). Besides NeuroD1, Sox2, Ngn2, and Ascl1 have all been reported to convert glial cells into neurons (Gascon et al, 2016;Grande et al, 2013;Guo et al, 2014;Heinrich et al, 2014;Liu et al, 2015;Niu et al, 2013;Su et al, 2014).…”
Section: Distinct Functions Of Neurod1 During Neuronal Conversionmentioning
confidence: 99%
“…Neuronal conversion can be achieved by several neurogenic transcription factors (Li and Chen, 2016 ). An earlier report also showed that Ngn2-expressing retrovirus was able to promote neurogenesis in the injured spinal cord, but the number of newly generated neurons greatly decreases over time even when combined with growth factor treatment (Ohori et al, 2006).…”
Section: Distinct Functions Of Neurod1 During Neuronal Conversionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we demonstrated that NeuroD1-mediated astrocyte reprogramming results in the production of mature, active and regionally appropriate neurons that survive long term and correlate with motor improvement following cortical stroke. Previous studies have demonstrated the feasibility of direct cellular conversion in vivo [7,9,[12][13][14][22][23][24][25] but few have demonstrated improved behavioural outcomes following injury [12,17]. Using a foot fault task and gait analysis, we demonstrate that astrocyte-to-neuron reprogramming leads to functional improvement as early as three weeks post-reprogramming, and sustained long-term recovery.…”
Section: Discussionmentioning
confidence: 75%
“…or of astrocytes through in vivo reprogramming [68] is a field under intense study and these vectors might have a distinct utility in this. Furthermore the stability of production and the lack of toxicity in producer cell lines or inactivation in human sera confers to these vectors the great advantage of being easily amenable for clinical use.…”
mentioning
confidence: 99%